THE URGENT AND YET FORGOTTEN PROBLEMS OF CURRENT SCIENTIFIC AND ACADEMIC PRACTICE: Os problemas urgentes e ainda esquecidos da prática científica e acadêmica atual - Carleial, Samuel; Soares, Marcelo (Arquivos de Ciências do Mar, 2022)
Science has an immense potential to change society such as by improving global public health or tackling climate change. This is especially important in the next 10 years (2021-2030) which are decisive for many countries around the globe to achieve the Sustainable Development Goals set by the United Nations. For this, the development of more science-based policies is crucial. However, a number of problems affect science nowadays. These problems are all well known, but little is being currently done to solve them. Here, we discuss the past and rising problems in the scientific and academic practice that need our urgent attention, namely the crises of accessibility, equity, reproducibility, credibility, deficiency in job opportunities and the vicious publication system. Additionally, we discuss current political and cultural problems such as the rise of fake news, clickbait videos, science denialism and misinformation that pose a threat not only to science practitioners, but also to the society at large. By acknowledging these crises, we propose that science can be improved for the benefit of the population in general (e.g., stakeholders, companies, governments, non-governmental organizations and traditional communities) and also for the very actors of science; the scientists and the new generations of academics. Keywords: ethics, fair science, open access, public policies, scientific production.